ANALISIS YURIDIS PERLINDUNGAN HUKUM PEREMPUAN DI BAWAH UMUR DALAM PERKAWINAN DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 16 TAHUN 2019 - Pangeran Ramadhan Putra; Niru Anita Sinaga (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
This study analyzes the legal protection of underage girls in marriage in Indonesia based on Law Number 16 of 2019. Although this law has raised the minimum age for marriage to 19 years, this study uses normative legal methods with case, statutory, and conceptual approaches, as well as qualitative analysis of legal materials. The practice of child marriage of girls remains high due to gaps in the marriage dispensation mechanism by the Religious Courts. Multiple interpretations of "urgent circumstances" in granting dispensations often override the principle of the child's best interests. Underage marriage has detrimental multidimensional impacts, including high reproductive health risks, obstacles to access to education and economic opportunities, and vulnerability to domestic violence (KDRT). Obstacles in the implementation of this legal protection are also exacerbated by strong socio-cultural factors (customs, stigma, patriarchy, low legal awareness), economic factors (poverty and limited access to education), as well as obstacles to law enforcement and institutions (limited resources, suboptimal coordination, inaccurate data, and potential intervention).